2022
DOI: 10.1093/ecco-jcc/jjac048
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Humoral Immune Responses to SARS-CoV-2 Vaccination in Inflammatory Bowel Disease Patients

Abstract: Background and Aims Knowledge on the immunogenicity of anti-SARS-CoV-2 vaccines in inflammatory bowel disease (IBD) patients is limited. Therefore, SARS-CoV-2-specific T-cell response and antibodies were analyzed in 60 IBD vaccine recipients and 30 controls. Methods SARS-CoV-2 IgG antibodies against the viral spike protein were measured at baseline and at 8 and 26 weeks after the second vaccine dose. SARS-CoV-2 IgG antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Among 60 patients with IBD from the Czech Republic, the CMIR, measured 26 weeks after the second dose with the IFN- γ–released assay response, was absent in 18% of patients, who were more likely to be on anti-TNF therapy. 29 Similar to the CLARITY IBD study, the study found an agreement between CMIR and antibody concentrations. In contrast, 2 other studies observed that most patients with IBD had a measurable CMIR.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Among 60 patients with IBD from the Czech Republic, the CMIR, measured 26 weeks after the second dose with the IFN- γ–released assay response, was absent in 18% of patients, who were more likely to be on anti-TNF therapy. 29 Similar to the CLARITY IBD study, the study found an agreement between CMIR and antibody concentrations. In contrast, 2 other studies observed that most patients with IBD had a measurable CMIR.…”
Section: Discussionsupporting
confidence: 66%
“… 31 Whether an inadequate CMIR also warrants an additional dose to the primary series for most patients with IBD is unknown. 12 , 29 After primary immunization, boosters should be administered as recommended for the general population. In fact, studies have shown robust antibody responses after 3 doses of COVID-19 vaccines in patients with IBD, with antibody concentrations being higher after the third dose than after the 2-dose primary series.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study reported that after two doses, a higher proportion of IBD patients lacked adequate SARS‐CoV‐2‐directed IFN‐γ secretion, when compared to healthy controls. 52 Importantly, this is the first study to demonstrate impaired functional T cell immunity in anti‐TNF‐treated IBD patients after three doses of SARS‐CoV‐2 mRNA vaccines. Interestingly, no correlation between humoral and T cell immunity was detected in this study (Figure 7A,B ).…”
Section: Discussionmentioning
confidence: 85%
“…Despite T lymphocytes being the key orchestrators of adaptive immune responses and conferring long-lasting protection through immune memory [ 29 , 30 ], their role in this setting is not well defined. In particular, the effects of immune-modifying treatments on cellular immune response in IBD patients following COVID-19 vaccination were poor and often controversial [ 31 , 32 , 33 , 34 , 35 ]. The imbalance of anti-SARS-CoV-2 vaccine effectiveness among two branches of adaptive immune responses could be due to the complexity of gold standard assays, which are unsuitable for clinical laboratory application.…”
Section: Introductionmentioning
confidence: 99%